Validity of Palmar Pallor for Diagnosis of Anemia among Children Aged 6–59 Months in North India. (9th November 2014) - Aggarwal, Arun Kumar; Tripathy, Jaya Prasad; Sharma, Deepak; Prabhu, Ajith
Abstract : Introduction. The Integrated Management of Childhood and Neonatal Illness (IMNCI) recommends the use palmar pallor to diagnose anaemia. Earlier studies to validate palmar pallor as clinical sign for anaemia were largely done in African context. There was a need to test validity of palmar pallor to detect anemia in different settings. Objective. To study the validity and interobserver agreement of palmar pallor examination to diagnose anemia in children under 5 years of age in India. Methods. In a village in Northern India, hemoglobin estimation was done for 80 children using cyanomethemoglobin method. Two examiners, a physician and a health worker, trained in IMNCI evaluated children for palmar pallor. Sensitivity and specificity and Kappa statistics were calculated. Results. Health worker diagnosed palmar pallor with sensitivity of 30.8–42.8% and specificity of 70–89%. Similar figures for doctor were 40–47% and 60–66%, respectively. Kappa agreement between a health worker and a physician was 0.48 (95% CI = 0.298–0.666) and then increased to 0.51 when categories of severe pallor and mild pallor were merged. Conclusion. While using palmar pallor as clinical sign for anaemia, children with no pallor should also be followed up closely for possible detection of missed cases during follow-up.